THE MECHANISM OF IMPLEMENTING ELECTRONIC MANAGEMENT AND ITS ROLE IN DEVELOPING ADMINISTRATIVE PERFORMANCE AMONG ADMINISTRATIVE AND TECHNICAL LEADERS IN SPORTS CLUBS - Asst. Prof. Dr. Zeyad Hameed Abd (Scholars Digest Publishing, 2025)
Abstract This study aims to identify the human and administrative obstacles hindering the implementation of electronic management in sports clubs. It also seeks to explore the financial and technical challenges associated with the adoption of electronic management systems, as well as to assess the extent to which electronic management contributes to the development of administrative performance within sports clubs. Furthermore, the study investigates strategies to overcome the challenges facing the implementation of electronic management in these institutions. The descriptive approach was employed, given its suitability for the nature of the research. The researcher developed a questionnaire comprising six main dimensions, encompassing a total of eighty items. The research sample consisted of 115 individuals distributed across various Iraqi sports clubs. The study concluded that there is an insufficient number of technical staff capable of operating modern electronic devices and communication technologies. Moreover, there is a lack of an organizational structure dedicated to electronic management within clubs, as well as inadequate financial allocations to organize lectures, seminars, and workshops related to electronic management applications. The study recommends the necessity of employing enough technicians proficient in handling all modern electronic devices and communication tools. It also emphasizes the importance of training staff to use electronic technologies effectively, appointing qualified personnel to manage electronic systems within clubs, increasing the number of human resources specialized in electronic management, organizing training courses on electronic management mechanisms for club staff, and providing adequate budget allocations for the acquisition of modern electronic technologies.
Keywords: Electronic Management, Administrative Performance, Administrative Leadership.